Antifungal effects of Streptococcus mutans extract on Candida strains susceptible and resistant to fluconazole: An in vivo study - Alves, Mariana De Sá [UNESP] (2021)
Previous studies showed that the crude extract obtained from Streptococcus mutans inhibited the growth of Candida albicans reference strains. In this study, we evaluated whether the antifungal effects of S. mutans extract can be extended to clinical Candida isolates, including C. albicans and non-abicans strains with different susceptibilities to fluconazole. We verified that S. mutans extract increased the survival of Galleria mellonella larvae infected with C. albicans and C. glabrata and inhibited the fungal cells in hemolymph. These antifungal effects occurred for both fluconazole-susceptible and fluconazole-resistant strains. However, larvae infected by C. krusei were not affected by S. mutans extract. Lay Summary: Streptococcus mutans crude extract shows antifungal effects on clinical Candida strains susceptible and resistant to fluconazole in Galleria mellonella model.